Machinability characterization in end milling of Invar 36 fabricated by wire arc additive manufacturing - Gil Del Val, Alain; Cearsolo, Xabier; Suarez, Alfredo; Veiga, Fernando; Altuna, Iker; Ortiz, Mikel (Journal of Materials Research and Technology, 2023)
Aircraft manufacturing sector manufactures a huge number of preforms near to the final profile or accuracy molds to avoid waste and to be more sustainable in terms of environ-ment. However, this near net shape (NNS) profiles need requirements to avoid expansions and contractions in the manufacturing process, restricted tolerances and high dimensional stability. Therefore, the aim of this paper is to propose a machinability characterization finished milling study of Invar 36 samples fabricated by Wire Arc Additive Manufacturing (WAAM) technology using Minimum Quantity Lubrication (MQL). The results state that the WAAM sample roughness values reach the smallest values for all the cutting conditions although the average WAAM sample force increment is 9% comparing the wrought one owing to the high hardness level of WAAM samples (20%). Moreover, not only the statistical analysis demonstrates that the cutting speed is irrelevant in this machinability investi-gation, but it also optimizes the best roughness value (0.8 mm) when milling at the cutting speed of 50 m/min and feed per tooth of 0.06 mm/z. Finally, the main wear mechanism when finished milling WAAM sample of Invar 36 is adhesion on the rake a clearance faces.(c)
Keywords: DED; WAAM; Invar 36; machinability; end milling; MQL; NNS; JCR; Scopus